Swords and Plowshares: Regional Trade Agreements and Political Conflict in Africa - Filippo Andreatta; Pier Giorgio Ardeni; Arrigo Pallotti (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2000)
The end of the Cold War and the apparent stability of the contemporary international system, in which the probability of a major war is at its lowest for centuries, have spurred a lively debate on the causes of peace. One of the most popular explanations is based on the classic liberal statement that economic interdependence reduces political conflict. Globalisation, narrowly defined as the increase in the quantity and quality of international economic exchanges experienced in the last few years, would then be one of the main reasons for international political stability. Even at the regional level, therefore, the increase in economic intercourse should bring, as a welcome political externality, the amelioration of international conflict. This view posits, for instance, that the emergence of a «zone of peace» within Western Europe has been brought about by the creation of a common market which has created a powerful incentive to avoid political conflict. Or that in other areas, such as Latin America, the recent increase in regional stability would rest on the launch of Mercosur and the greater interdependence that it has brought about. The hypothesis is that Regional Trade Agreements (RTAs) facilitate economic interdependence, which in turn facilitate political stability. In this paper we apply this hypothesis to the African case where a significant number of RTAs has been created in the last decades. Expectations of increased political stability have not, however, been confirmed. This does not necessarily undermine the general proposition of a positive correlation between interdependence and peace, but it does suggest that the relationship between the two elements may be more complicated than often acknowledged. On the one hand, African RTAs may simply not have produced the necessary level of trade and investment for a significant modification of political preferences. On the other hand, interdependence may be a necessary condition for peace, but it may also be insufficient, as its full impact on political preferences may require specific domestic institutions.
Keywords: 330